Seawater and wastewater from shrimp production as alternatives in the fermentation of fruit residue for ethanol production - Bonatto, Charline (2020)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2020.